Navigating an American College of Surgeons Virtual Verification Review Committee Visit: A Health System Perspective. Issue 6 (November 2021) - Marden, Edie; Christopherson, Nathan
Abstract : Background: Faced with a global pandemic at the beginning of 2020, the American College of Surgeons Committee on Trauma (ACS-COT) canceled in-person site visits. Late in 2020, the focus shifted to recovery and returning to a "new normal, " and the ACS transitioned to virtual visits. Objective: This article provides insight from a health system perspective on how we developed a virtual platform, prepared our system and staff, organized our teams, and lessons learned during virtual ACS visits. Methods: The Northwell Health Trauma Institute, a member of the largest health system in New York State, oversees seven centers ranging from Level I to Level III, including two pediatric centers. Preparations for virtual visits began with standardizing processes to ensure a smooth transition for our centers. We utilized the ACS virtual agenda as a framework. The methods we used will be divided into categories, including technology, personnel, and preparations. Results: Having multiple sites engage in the virtual visit enabled us to gain insight as we completed each visit. We standardized processes and created a team site for uploading documents. As a result, we established best practices. Conclusion: Shifting focus from an in-person visit to a virtual visit provided us with an opportunity to assess our preparations and to determine the most effective and efficient ways to navigate this new process. Having multiple sites allowed us to critique our process and make changes as we proceeded with subsequent sites.